KONTRIBUSI MINAT BACA DAN MEMBACA PEMAHAMAN TERHADAP KETERAMPILAN MENULIS ARGUMENTATIF SISWA KELAS X SMA SEMEN PADANG - Putri, Mega (English Department FBS UNP, 2011)
The research based on observation in the field. The result of this research is students at grade x still low in writing argumentative text. The was difficulties to developed the idea and fact to support a argumentative paragraph. This phenomena appear because student in reading ability and understanding is very low. Based on the problem above, the researcher need to describe contribution of reading ability and understanding in writing argumentative text on X grade students at SMA Semen Padang. The hypothesis in this research is contribution reading ability toward writing argumentative is very significance, contribution in understanding toward writing argumentative tex, contribution reading ability and understanding join together in writing argumentative text. The researcher can conclude that reading ability and comprehension have two factors in writing argumentative text on x grade students at sma semen padang, eventhough others factor the research do not research in this thesis. The result of this research is to increase the student writing x grade at SMA Semen Padang in reading ability and comprehension.